Pengaruh Penggunaan Metode Takrir Dan Taqlil Terhadap Kualitas Hafalan Al-Qur’an Di Yayasan Tahfidz Adawiyah Binti Abdurrahman - Nurriyani Siagian; Widya Masitah (Yayasan Rahmat Islamiyah, 2022)
This study is aimed at learning how the use of takrir and taqlil methods has affected the memorized qualities of the Qur’an. The study used 30 santri's samples. With a small population population, this research makes the entire population a study sample.It belongs to quantitative research. The study employed several techniques of data collection, observation, angket, and documentation. As for quantitative data analysis techniques using formulas of validity, reability, linear regression equations, classic assumptions test, hypothetical tests (t and determinations). The results of this study as follows: First, the results of the t-test suggest that takrir and taqlil's methods have significant influence on the qur 'an qualitative variables, Second, the r square of 0.341 which has the sense that memorized quality variables of the Koran are influenced together by 34.1%, while the rest of the 65.9% are affected by variables that do not exist in the study.